Structural characterization of CD81–Claudin-1 hepatitis C virus receptor complexes. (22nd March 2011) - Bonander, Nicklas; Jamshad, Mohammed; Hu, Ke; Farquhar, Michelle J.; Stamataki, Zania; Balfe, Peter; McKeating, Jane A.; Bill, Roslyn M.
Abstract : Tetraspanins are thought to exert their biological function(s) by co-ordinating the lateral movement and trafficking of associated molecules into tetraspanin-enriched microdomains. A second four-TM (transmembrane) domain protein family, the Claudin superfamily, is the major structural component of cellular TJs (tight junctions). Although the Claudin family displays low sequence homology and appears to be evolutionarily distinct from the tetraspanins, CD81 and Claudin-1 are critical molecules defining HCV (hepatitis C virus) entry; we recently demonstrated that CD81–Claudin-1 complexes have an essential role in this process. To understand the molecular basis of CD81–Claudin-1 complex formation, we produced and purified milligram quantities of full-length CD81 and Claudin-1, alone and in complex, in both detergent and lipid contexts. Structural characterization of these purified proteins will allow us to define the mechanism(s) underlying virus–cell interactions and aid the design of therapeutic agents targeting early steps in the viral life cycle.